고엽제 노출과 병원 밖 심정지 후 생존 퇴원과의 연관성 - 김동욱; Dong Wook Kim; 계유찬; Yu Chan Kye; 이정엽; Jung Youp Lee; 정의기; Eui Gi Jung; 김동성; Dong Sung Kim; 최현정; Hyun Jung Choi; et al. (대한임상독성학회지, 2021)
Purpose: We investigated the association between defoliant exposure and survival to discharge after out-of-hospital cardiac arrest. Methods: This is a retrospective case-control study based on the cardiopulmonary resuscitation (CPR) registry. The electronic medical records of out-of-hospital cardiac arrest victims from 6/9/2008 to 12/31/2016 were analyzed statistically. The case patients group had a history of defoliant exposure while the control group did not. Among the 401 victims studied, a total of 110 patients were male out-of-hospital cardiac arrest patients. Baseline characteristics and the parameters involved in cardiac arrest were analyzed and compared between the two groups after propensity score matching. The primary outcome was survival to discharge, and secondary outcomes were sustained return of spontaneous circulation (ROSC) and survival to admission. Results: After propensity score matching a total of 50 patients (case=25, control=25) were analyzed. Primary outcome (survival to discharge) was not significantly different between case and control groups [(OR, 1.759; 95% C.I., 0.491-6.309) and (OR, 1.842; 95% C.I., 0.515-6.593), respectively]. In the subgroup analysis, there were also no significant differences between the control group and subgroups in primary and secondary outcomes according to defoliant exposure severity. Conclusion: There is no statistically significant association between defoliant exposure and survival of out-of-hospital cardiac arrest.